2010
DOI: 10.1074/jbc.m110.164863
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ-mediated Inhibition of Serum Response Factor-dependent Smooth Muscle-specific Gene Expression

Abstract: IFN␥ exerts multiple biological effects on effector cells by regulating many downstream genes, including smooth muscle-specific genes. However, the molecular mechanisms underlying IFN␥-induced inhibition of smooth muscle-specific gene expression remain unclear. In this study, we have shown that serum response factor (SRF), a common transcriptional factor important in cell proliferation, migration, and differentiation, is targeted by IFN␥ in a STAT1-dependent manner. We show that the molecular mechanism by whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 37 publications
2
29
1
Order By: Relevance
“…This result demonstrated the RNase L-dependent down-regulation of TTP transcription (81,82) in mitogenstimulated MEFs and suggested that RNase L directly targets a transcription factor that mediates TTP induction by mitogens. Consistent with this model, SRF is a master transcriptional regulator of serum-induced genes that was previously reported to be regulated by RNase L in IFN␥-stimulated smooth muscle cells (66). Furthermore, analysis of the ZFP36/TTP gene promoter revealed a serum-response element, the site at which SRF binds to induce transcription of mitogen-induced genes, at positions Ϫ281 to Ͼ264 relative to the ZFP36/TTP transcription start site (83).…”
Section: Rnase L Down-regulates Mitogen-induced Ttp Transcription Viasupporting
confidence: 52%
See 2 more Smart Citations
“…This result demonstrated the RNase L-dependent down-regulation of TTP transcription (81,82) in mitogenstimulated MEFs and suggested that RNase L directly targets a transcription factor that mediates TTP induction by mitogens. Consistent with this model, SRF is a master transcriptional regulator of serum-induced genes that was previously reported to be regulated by RNase L in IFN␥-stimulated smooth muscle cells (66). Furthermore, analysis of the ZFP36/TTP gene promoter revealed a serum-response element, the site at which SRF binds to induce transcription of mitogen-induced genes, at positions Ϫ281 to Ͼ264 relative to the ZFP36/TTP transcription start site (83).…”
Section: Rnase L Down-regulates Mitogen-induced Ttp Transcription Viasupporting
confidence: 52%
“…A binding site for the serum-response factor (SRF), a master transcriptional regulator of serum-induced genes, was identified in the ZFP36 gene promoter. Furthermore, SRF mRNA was previously reported to be down-regulated by RNase L in IFN␥-stimulated mouse embryo fibroblasts (MEFs) (66). Together, these observations suggested that SRF mRNA is a direct target of RNase L and that this regulation may account for the RNase L-dependent regulation of TTP in mitogen-stimulated cells.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…For example, transforming growth factor beta-1 (TGF-β1) the most profibrogenic cytokine for stellate cells, may also regulate smooth muscle α actin gene expression [37]. Recent evidence indicates that smooth muscle α actin expression in stellate cells is controlled transcriptionally by canonical muscle specific transcription factors, including serum response factor [38]. Further, it appears that there may be interplay between the smooth muscle α actin cytoskeleton and various stellate cell functions, including cell motility and contractility [39].…”
Section: Intrahepatic Vascular Pathophysiologymentioning
confidence: 99%
“…The molecular mechanism of upregulation of these smooth muscle contractile proteins appears to be via a robust smooth muscle transcriptional program, including upregulation of a family of transcription factors important in smooth muscle cell biology [13]. Although controversy exists regarding the magnitude of contraction of normal stellate cells, available data emphasize that stellate cells in the injured liver exhibit enhanced contractility and moreover, the degree of contraction appears to be proportional to the degree of liver injury [14,15].…”
Section: Overviewmentioning
confidence: 98%